2014
DOI: 10.1371/journal.pone.0104529
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor Mediates a Switch in Intracellular Signaling for PGE2-Induced Sensitization of Sensory Neurons from Protein Kinase A to Epac

Abstract: We examined whether nerve growth factor (NGF), an inflammatory mediator that contributes to chronic hypersensitivity, alters the intracellular signaling that mediates the sensitizing actions of PGE2 from activation of protein kinase A (PKA) to exchange proteins directly activated by cAMP (Epacs). When isolated sensory neurons are grown in the absence of added NGF, but not in cultures grown with 30 ng/ml NGF, inhibiting protein kinase A (PKA) activity blocks the ability of PGE2 to augment capsaicin-evoked relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 87 publications
1
33
1
Order By: Relevance
“…Conversely, intraplantar administration of the Epac agonist 8-pCPT induces mechanical hyperalgesia (6,7,16,27). In vitro, ESI-09 inhibits both Epac1 and Epac2 (27,28), and there is evidence that both Epac1 (7) and Epac2 (29) contribute to sensitization of painsensing neurons. We demonstrate here that Epac1 −/− mice are protected from mechanical hyperalgesia in the CFA model of inflammatory pain and that these mice are also protected against neuropathic pain (7).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, intraplantar administration of the Epac agonist 8-pCPT induces mechanical hyperalgesia (6,7,16,27). In vitro, ESI-09 inhibits both Epac1 and Epac2 (27,28), and there is evidence that both Epac1 (7) and Epac2 (29) contribute to sensitization of painsensing neurons. We demonstrate here that Epac1 −/− mice are protected from mechanical hyperalgesia in the CFA model of inflammatory pain and that these mice are also protected against neuropathic pain (7).…”
Section: Discussionmentioning
confidence: 99%
“…Different cAMP affinities and activation paradigms suggest that stimulation of Gs protein coupled receptors will initially activate PKA with EPAC signaling following only with greater/stronger receptor activation. However, certain growth/trophic factors can change the relative cAMP sensitivity of PKA and EPAC, shifting activation thresholds in favor of EPAC signaling (Vasko et al, 2014). For example, although nerve growth factor-1 (NGF-1) does not affect plasticity expression in a well-studied model of sensory hypersensitivity, it does convert the plasticity from PKA- to EPAC-dependence (Vasko et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, certain growth/trophic factors can change the relative cAMP sensitivity of PKA and EPAC, shifting activation thresholds in favor of EPAC signaling (Vasko et al, 2014). For example, although nerve growth factor-1 (NGF-1) does not affect plasticity expression in a well-studied model of sensory hypersensitivity, it does convert the plasticity from PKA- to EPAC-dependence (Vasko et al, 2014). Similar effects could shift the PKA/EPAC balance downstream from 5-HT 7 receptors, enable 5-HT 7 receptors to contribute rather than constrain serotonin-induced plasticity, potentially explaining enhanced serotonin-dependent plasticity observed with preconditioning experiences known to increase growth/trophic factor expression (Kinkead et al, 1998; Johnson et al, 2000; Ling et al, 2001; Wilkerson and Mitchell, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that activation of Epacs enhances nociceptive behaviors (Hucho et al, 2005) and mediates the prostaglandin-induced sensitization of sensory neurons after inflammation or exposure to NGF (Vasko et al, 2014). To determine whether direct activation of Epacs sensitizes peptidergic sensory neurons, we assessed whether treatment with the selective Epac agonist, 8CPT-AM (Holz et al, 2008) augmented the evoked release of iCGRP from sensory neurons.…”
Section: Resultsmentioning
confidence: 99%
“…For example, acute exposure to prostaglandin E2 (PGE2) produces hyperalgesia and an increase in the excitability of sensory neurons, which are both mediated by increases in cAMP and activation of protein kinase A (PKA) (Aley and Levine, 1999; England et al, 1996; Hingtgen et al, 1995; Lopshire and Nicol, 1998; Sachs et al, 2009). With inflammation, or when sensory neurons are maintained in the presence of the inflammatory mediator, nerve growth factor (NGF), the sensitization induced by subsequent administration of PGE2 shifts from using PKA as the primary effector to activation of Epacs (Eijkelkamp et al, 2013; Hucho et al, 2005; Vasko et al, 2014; Wang et al, 2007). …”
Section: Introductionmentioning
confidence: 99%